Sliding Mode Control: The Delta-Sigma Modulation Approach - Hu, Hesuan (2017)
Sliding-mode control is one of the well-recognized non-linear control methods for nonlinear systems. The sliding mode controller can modify the dynamics of a nonlinear system by the application of a discontinuous feedback control technique, leading to the evolution of the state trajectory along an intersection manifold. A key feature in sliding-mode control is its discontinuous feedback control techniques, which take values in a discrete rather than continuous set. This property allows the closed-loop system to switch from one continuous structure to another in the state space. By translating the desired control objectives into single or multiple constraints in the state space, the feedback mechanism is expected to generate a state trajectory that satisfies all these constraints simultaneously. The objective of this book is to present fundamental knowledge about sliding-mode control as well as the most recent developments in theory and applications. To be comprehensible, diverse examples are employed to demonstrate applicability in numerous areas. The author endeavors to make the theoretical parts as concise as possible and to make the applications as comprehensive as possible. The book is a valuable textbook for beginners in sliding-mode control. It can also be a reference for experienced researchers in both academia and industry. This book can be used in senior undergraduate- and/or graduate-level courses. The text starts from simple but explanatory examples, complements examples with intuitive but introductory theories, and concludes with recent advanced developments, therefore achieving a coherent presentation. Except for some rarely used terms, most material in the presentation is self-contained. Readers can refer to some easily accessible references to further pursue the relevant topics of interest. Inarguably, there are some editing typos and grammatical errors as well as some insufficiently described technical concepts. However, none of these hinder the book’s overall understandability since readers can correctly grasp the intended meaning from the context.